2001
DOI: 10.1016/s0167-4889(00)00141-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of proteasome and redox state on heat shock-induced activation of stress kinases, AP-1 and HSF

Abstract: We studied the pattern of activation of stress kinases and of transcription factors activator protein-1 (AP-1) and heat shock factor (HSF) in FAO cells by combining two treatments, i.e. heating (42 degrees C for 1 h) and proteasome inhibition, each known to cause cellular heat shock response. The co-treatment heat shock (HS) and proteasome inhibitor (a peptidyl aldehyde or lactacystin) showed cumulative effects on the intensity and duration of activation of c-Jun N-terminal kinase (JNK) and p38 mitogen-activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…ATP-dependent HSP90 was shown to protect the trypsin-like activity of the proteasome system from oxidative inactivation (9) and to inhibit the activity of the proteasome (4,15,33). Proteasome inhibitors activate heat shock transcription factors, with the subsequent induction of HSPs (55,56); e.g., the exposure of U373 MG human glioma cells to proteasome inhibitors induces HSF2-mediated accumulation of HSP27 (38). In the present study, we identified another relationship between the ubiquitin-proteasome pathway and HSP27.…”
Section: Discussionmentioning
confidence: 99%
“…ATP-dependent HSP90 was shown to protect the trypsin-like activity of the proteasome system from oxidative inactivation (9) and to inhibit the activity of the proteasome (4,15,33). Proteasome inhibitors activate heat shock transcription factors, with the subsequent induction of HSPs (55,56); e.g., the exposure of U373 MG human glioma cells to proteasome inhibitors induces HSF2-mediated accumulation of HSP27 (38). In the present study, we identified another relationship between the ubiquitin-proteasome pathway and HSP27.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown that cells respond to exposure to elevated temperatures by increasing production of Hsps (heat‐shock proteins) such as Hsp70, Hsp27 and Akt (also known as protein kinase B) [23,27]. p38 MAPK, a member of the family of MAPKs, is essential for the triggering of Hsp expression by heat stress [7,24,28]. Various physical stimuli have been demonstrated to activate p38 MAPK [7], suggesting that activation of p38 MAPK is an essential step for formation of an HA‐mediated 3D‐like proliferation pattern of mouse fibroblasts in response to physical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…36 For these reasons, activation of stress-related cascades is one of the factors thought to be involved in proteasome inhibitor-mediated lethality. 37 Moreover, interference with MEK/ERK signaling (ie, by pharmacologic MEK inhibitors) has recently been shown to promote the lethal actions of proteasome inhibitors. 38 It is noteworthy that exposure of K562 cells to HDIs resulted in down-regulation of the Raf/MEK/ERK cascade, in agreement with previous reports demonstrating similar events in depsipeptide-treated non-small cell lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%